Determinación del porcentaje de gestación en vacas empleando inseminación artificial a tiempo fijo (IATF) con la optimización de pajuelas de semen en un 200 y 300% en el cantón Saraguro - Guamán Poma, Marco Vicente (2024)
In a genetic improvement plan, the biotechnological technique of Artificial Insemination is a tool that allows us to improve milk progeny, as is the case of this Research. The economic cost of using straws with good genetic characteristics is high, and they are used on select cows by the producer, often failing in their pregnancy rate, which leads to an economic loss and loss of genetic material, hence with. The present research work aims to optimize the use of a straw of high genetic value that has a high economic cost, in 2 and 3 females, thereby reducing the risks of failure in conception rates. The specific objectives of the research were: Determine pregnancy in treatments T1, T2, T3; Obtain the cost of a pregnant cow in treatments T1, T2, T3 and Evaluate the semen quality of the semen used in the research. The work was carried out in the province of Loja, Saraguro canton, 18 dairy cattle females were used, the P4 and eCG Protocols were used to synchronize heat. In T1,3 straws/3 cows were used, with a pregnancy rate of 67%; T2 with 3 Straws /6 cows, presenting 33% pregnancy; T3 with 3 straws/9 cows, showed a pregnancy rate of 56%. Meanwhile, in the statistical analysis with a valuation (P: 0.049), there is a significant difference between the treatments. In the 18 experimental Units, $792.18 USD was invested, T1 with a cost of ($162.03); T2 cost ($264.06 USD; T3 with an investment ($366.09 USD). Considering that between T2 and T3 the cost did not significantly influence in contrast to T1, there is a clear difference. The straw was used with a concentration of 19.82 M/mL, with a Volume of 0.50 mL, viability of live spermatozoa 46% and dead spermatozoa 54%; in the study of normal morphological abnormalities 91% and individual motilities of 43.88%.